Forced and chosen transfers for medical assistance in dying (MAiD) before and during the COVID 19 pandemic: A mixed methods study. Issue 9 (21st October 2022) - Wiebe, Ellen; Sum, Brian; Kelly, Michaela; Hennawy, Mirna
Abstract: The purpose of this study was to describe the experience of people who transferred locations for MAiD. It used mixed methods with a chart review from one health authority and interviews with key informants across Canada. In the chart review, we found that of 444 MAiD deaths, 42 (9.5%) were forced to transfer due to the religious affiliation of the facility and 33 (7.4%) chose to transfer. In 23 interviews with 18 key informants we found that the most important theme was the suffering caused by forced transfers. COVID-19 restrictions led to fewer choices and more suffering.